2016
DOI: 10.1002/adfm.201603454
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Approach for High‐Efficiency Photoelectrochemical Solar Cells by Using Bifunctional DNA Molecules Modified Photoanode

Abstract: wileyonlinelibrary.comadsorption and relatively high recombination rate via vacant sites that significantly restrict the photoconversion efficiency (PCE). Therefore, researchers are faced with the challenge of developing efficient suppression routes by designing this component with an efficient charge transport pathway. Although some approaches were reported to suppress the charge recombinations occurring at the TiO 2 /dye interface including the use of inorganic [3,4] as well as polymer-assisted materials, [5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…These elongated structures, with an average lateral distance of 1–6 nm, contain several DNA strands. Furthermore, Sönmezoğlu et al have reported highly efficient dye‐sensitized solar cells with a DNA modified ITO photoanode, in which the double‐helix of the DNA acts as linker bridging unit between the active layer and the ITO. Thus we postulate that when the P3HT polymer is spin coated on our ITO/ZnO‐NPs/DNA, the elongated strands of DNA chemically interact with the polymer strands leading to a more ordered layer as the solvent evaporates.…”
Section: Resultsmentioning
confidence: 99%
“…These elongated structures, with an average lateral distance of 1–6 nm, contain several DNA strands. Furthermore, Sönmezoğlu et al have reported highly efficient dye‐sensitized solar cells with a DNA modified ITO photoanode, in which the double‐helix of the DNA acts as linker bridging unit between the active layer and the ITO. Thus we postulate that when the P3HT polymer is spin coated on our ITO/ZnO‐NPs/DNA, the elongated strands of DNA chemically interact with the polymer strands leading to a more ordered layer as the solvent evaporates.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning electrodes/substrates the materials and approaches developed in OSCs have been also applied to DSSCs. [160][161][162] More innovative ideas toward bio-based dyes and electrolytes are present in the prior art. In short, the design of dyes for highly performing DSSCs should fulfill several requirements: i) high molar extinction coefficient, ii) broadband absorption spectra covering visible and Near-IR range, iii) strong binding or electron coupling with the mesoporous semiconductor, iv) alignment of energy levels, with regard to the conduction band of the semiconductor and the redox couple potential, and v) stability upon continuous sunlight exposition.…”
Section: Dsscsmentioning
confidence: 99%
“…Therefore, the observed reduction in R ct in this work can also occur due to the amine‐modified ssDNA covalently bonding with the aldehyde groups on the 3,4‐dihydroxybenzlaldehyde (DHBA) linker on the TiO 2 NP surface having the same linker chemistry as dopamine, thereby enhancing the probability of quantum tunneling. It has also been hypothesized that DNA functionalization reduces carrier trapping sites by passivating the semiconductor (TiO 2 ) surface, thereby reducing charge recombination [47] . In order to further validate this finding, we performed a study by performing cyclic voltammetry (CV) in 0.1 M phosphate buffer (PBS) to show changes in charge transfer kinetics (Supporting Figure S3).…”
Section: Resultsmentioning
confidence: 90%
“…Forschungsartikel linker chemistry as dopamine,t hereby enhancing the probability of quantum tunneling.I th as also been hypothesized that DNAf unctionalization reduces carrier trapping sites by passivating the semiconductor (TiO 2 )surface,thereby reducing charge recombination. [47] In order to further validate this finding,w ep erformed as tudy by performing cyclic voltammetry (CV) in 0.1 Mphosphate buffer (PBS) to show changes in charge transfer kinetics (Supporting Figure S3). This study showed that the amount of stored charges in the photoelectrodes were increased from 0.59 mC to 0.72 mC after DNAf unctionalization, indicating longer lived excitons.…”
Section: Angewandte Chemiementioning
confidence: 99%